Efficient bulk heterojunction solar cells based on solution processed small molecules based on the same benzo[1, 2-b:4, 5-b′]thiophene unit as core donor and different terminal units. Issue 17 (2nd April 2015) - Vijay Kumar, Challuri; Cabau, Lydia; Koukaras, Emmanuel N.; Siddiqui, Shahbaz A.; Sharma, Ganesh D.; Palomares, Emilio
Abstract : Two novel molecules, DRT3-BDT andDTT3-BDT, based on a BDT central core (donor) and with different edge acceptor units linked via a terthiophene π-conjugation bridge, have been synthesized. Abstract : We report the synthesis, characterization, and optical and electrochemical of properties of two novel moleculesDRT3-BDT (1) andDTT3-BDT (2), comprising the same BDT central core (donor) and different end capped acceptor units, i.e. rhodanine with ethyl hexyl and thiazolidione with ethylhexyl, respectively, linked via an alkyl-substituted terthiophene (3 T) π-conjugation bridge. The electrochemical properties of these small molecules indicate that their energy levels are compatible with energy levels of PC71 BM for efficient exciton dissociation. These molecules have been used as electron donors along with PC71 BM as an electron acceptor, for the fabrication of solution processed "small molecule" bulk heterojunction (BHJ) solar cells (smOPV). The device prepared from optimized1  : PC71 BM(1 : 1) processed cast from DIO (3%v)/CF solvent exhibited a power conversion efficiency of 6.76% with J sc = 11.92 mA cm −2, V oc = 0.90 and FF = 0.63. The device with2  : PC71 BM under the same conditions showed a lower PCE of 5.25% with J sc = 10.52 mA cm −2, V oc = 0.86 and FF = 0.56. The AFM, TEM and PL quenching measurements revealed that the high J sc is a result of the appropriate morphology and exciton dissociation. The performances were compared for the devices based on two small molecules. The higher J sc for device1 was attributed to its better nanoscale phase separation, smooth surface and higher carrier mobility in the1  : PC71 BM blend film. Moreover, the higher value of FF for the1  : PC71 BM based device was ascribed to a good balance between the electron and hole mobilities.